Is being diagnosed at a dedicated breast assessment unit associated with a reduction in the time to diagnosis for symptomatic breast cancer patients?. (5th June 2018) - Jiang, Li; Gilbert, Julie; Langley, Hugh; Moineddin, Rahim; Groome, Patti A.
Abstract: The length of the cancer diagnostic interval can affect a patient's survival and psychosocial well‐being. Ontario Diagnostic Assessment Units (DAUs) were designed to expedite the diagnostic process through coordinated care. We examined the effect of DAUs on the diagnostic interval among female patients with symptomatic breast cancer in Ontario using the Ontario Cancer Registry linked to administrative healthcare data. The diagnostic interval was defined as the time from patients' first referral or test to the cancer diagnosis. DAU use was determined based on the hospital where the breast biopsy/surgery was performed. Multivariable quantile regression and logistic regression analyses adjusted for possible confounders. Forty‐seven per cent of patients were diagnosed in a DAU and 53% in usual care (UC). DAUs achieved the Canadian timeliness targets more often than UC (71.7% vs. 58.1%, respectively). DAU use was associated with a 10‐day (95% CI: 7.8–11.9) reduction in the median diagnostic interval. This effect increased to 19 days for patients at the 75th percentile and 22 days for those at the 90th percentile of the diagnostic interval distribution. Use of an Ontario DAU is associated with a shorter time to diagnosis in patients with symptomatic breast cancer, especially for those who would otherwise wait the longest.